Real-time imaging of skeletal muscle velocity - Asakawa, Deanna S.; Nayak, Krishna S.; Blemker, Silvia S.; Delp, Scott L.; Pauly, John M.; Nishimura, Dwight G.; Gold, Garry E. (Journal of magnetic resonance imaging, 2003)
Purpose To test the feasibility of using real‐time phase contrast (PC) magnetic resonance imaging (MRI) to track velocities (1–20 cm/second) of skeletal muscle motion. Materials and Methods To do this we modified a fast real‐time spiral PC pulse sequence to accommodate through‐plane velocity encoding in the range of −20 to +20 cm/second. We successfully imaged motion of the biceps brachii and triceps brachii muscles during elbow flexion and extension in seven unimpaired adult subjects using real‐time PC MRI. Results The velocity data demonstrate that the biceps brachii and the triceps brachii, antagonistic muscles, move in opposite directions during elbow flexion and extension with velocity values in the muscle tissue ranging from –10 to +10 cm/second. Conclusion With further development, real‐time PC MRI may provide a means to analyze muscle function in individuals with neurologic or movement disorders who cannot actively complete the repeated motions required for dynamic MRI techniques, such as cine PC MRI, that are more commonly used in musculoskeletal biomechanics applications. J. Magn. Reson. Imaging 2003;18:734–739. © 2003 Wiley‐Liss, Inc.